(untitled) (Journal of Engineering, 2017)
Storage tanks condition and integrity is maintained by joint application of coating and cathodic protection. Iraq southern region rich in oil and petroleum product refineries need and use plenty of aboveground storage tanks. Iraq went through conflicts over the past thirty five years resulting in holding the oil industry infrastructure behind regarding maintenance and modernization. The primary concern in this work is the design and implementation of cathodic protection systems for the aboveground storage tanks farm in the oil industry. Storage tank external base area and tank internal surface area are to be protected against corrosion using impressed current and sacrificial anode cathodic protection systems. Interactive versatile computer programs are developed to provide the necessary system parameters data including the anode requirements, composition, rating, configuration, etc. Microsoft-Excel datasheet and Visual Basic.Net developed software were used throughout the study in the design of both cathodic protection systems. The case study considered in this work is the eleven aboveground storage tanks farm situated in al-Shauiba refinery in southern IRAQ. The designed cathodic protection systems are to be installed and monitored realistically in the near future. Both systems were designed for a life span of (15-30) years, and all their parameters were within the internationally accepted standards.